Vascular markers among young women with CVD risk factors - Amilia Aminuddin,; Azizah Ugusman,; Norizam Salamt,; Musilawati Muhajir, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Data pertaining to carotid intima-media thickness (CIMT), carotid-femoral pulse wave velocity (PWVcf), augmentation index (AI), and C-reactive protein (CRP) are less studied among young Asian women. The objectives of this study were to determine the associations between these vascular markers with other cardiovascular (CVD) risk factors and future CVD risks; and secondly, to determine the associations between the markers themselves among young women. One hundred and forty-eight young women who were healthy, or having any CVD risk factor, were recruited. They were divided into a healthy group (HG, n=71) and a risk group (RG, n=77). The parameters measured included body anthropometry, blood pressure (BP), CIMT, PWVcf, AI, CRP, blood sugar, and lipid profiles. The future CVD risk was expressed in short and long term Framingham Risk Scores (FRS). The data was analysed via SPSS and p-value <0.05 was accepted as significant. The RG had significantly higher PWVcf, AI, and hs-CRP when compared to HG. All of the markers were associated with CVD risk factors and the long-term FRS. The independent variable for CIMT was age (R2=0.11), while PWVcf was determined by diastolic BP and age (R2=0.29). AI was independently determined by age, heart rate, and LDL (R2=0.28), while for CRP, it was weight and HDL (R2=0.30). In conclusion, among the young women with CVD risk factor, CIMT, PWVcf, AI, and hs-CRP can be used to assess their risk of future CVD. No associations were observed between the markers themselves, which suggests that every marker reflects a different entity. They should be measured independently for a complete vascular assessment.